2008
DOI: 10.1016/j.joen.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ProTaper Universal Retreatment Files in Removing Filling Materials during Root Canal Retreatment

Abstract: The aim of this study was to evaluate the efficacy of the ProTaper Universal System rotary retreatment system and of Profile 0.06 and hand instruments (K-file) in the removal of root filling materials. Forty-two extracted single-rooted anterior teeth were selected. The root canals were enlarged with nickel-titanium (NiTi) rotary files, filled with gutta-percha and sealer, and randomly divided into 3 experimental groups. The filling materials were removed with solvent in conjunction with one of the following de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
144
1
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(174 citation statements)
references
References 28 publications
13
144
1
16
Order By: Relevance
“…The use of a solvent has been suggested to reduce the sealer microhardness, facilitating NiTi instrument insertion into filling material (31), shortening the retreatment time (32). Although the use of solvent is recommended (33), the chemically softened gutta-percha can be forced into root canal walls and into its complex anatomy that is not touched by the instruments, increasing the challenges for filling removal and possibly increasing the instrumentation time (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a solvent has been suggested to reduce the sealer microhardness, facilitating NiTi instrument insertion into filling material (31), shortening the retreatment time (32). Although the use of solvent is recommended (33), the chemically softened gutta-percha can be forced into root canal walls and into its complex anatomy that is not touched by the instruments, increasing the challenges for filling removal and possibly increasing the instrumentation time (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been proposed for removing root filling material, but none have shown the ability to remove gutta-percha and sealer completely from canal walls 8,9,11 . The removal of gutta-percha by using hand instruments is a slow and difficult process, especially when the filling material is well compacted.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of gutta-percha by using hand instruments is a slow and difficult process, especially when the filling material is well compacted. Thus, Ni-Ti rotary instruments are recommended for reducing clinical time and facilitate removal 9,11 . However, in this study, we observed that even after using Ni-Ti rotary instruments specifically developed for retreatment, the filling material was not completely removed from the root canal walls, corroborating the findings of other studies 7,9-11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations